Cobalt nanoparticles trigger ferroptosis‐like cell death (oxytosis) in neuronal cells: Potential implications for neurodegenerative disease. Issue 4 (14th February 2020) - Gupta, Govind; Gliga, Anda; Hedberg, Jonas; Serra, Angela; Greco, Dario; Odnevall Wallinder, Inger; Fadeel, Bengt
Abstract: The neurotoxicity of hard metal‐based nanoparticles (NPs) remains poorly understood. Here, we deployed the human neuroblastoma cell line SH‐SY5Y differentiated or not into dopaminergic‐ and cholinergic‐like neurons to study the impact of tungsten carbide (WC) NPs, WC NPs sintered with cobalt (Co), or Co NPs versus soluble CoCl2 . Co NPs and Co salt triggered a dose‐dependent cytotoxicity with an increase in cytosolic calcium, lipid peroxidation, and depletion of glutathione (GSH). Co NPs and Co salt also suppressed glutathione peroxidase 4 (GPX4) mRNA and protein expression. Co‐exposed cells were rescued by N‐acetylcysteine (NAC), a precursor of GSH, and partially by liproxstatin‐1, an inhibitor of lipid peroxidation. Furthermore, in silico analyses predicted a significant correlation, based on similarities in gene expression profiles, between Co‐containing NPs and Parkinson's disease, and changes in the expression of selected genes were validated by RT‐PCR. Finally, experiments using primary human dopaminergic neurons demonstrated cytotoxicity and GSH depletion in response to Co NPs and CoCl2 with loss of axonal integrity. Overall, these data point to a marked neurotoxic potential of Co‐based but not WC NPs and show that neuronal cell death may occur through a ferroptosis‐like mechanism.